RESEARCH ON CUSTOMER’S SATISFACTION FOR THE 4P’S PIZZA RESTAURANT IN HANOI - Le, Mai Mai (Khoa Quốc tế, ĐHQGHN, 2019)
After the success of two Pizza 4P’s restaurants in Saigon, Pizza 4P’s had a branch in Hanoi for the first time in July, 2017. Bringing a new taste of pizza to Hanoi customers, it is a combination of the Italian-style dishes and the Japanese-style service. After nearly a year of appearance in Hanoi with a completely new menu from the existing pizza restaurants, perhaps apart from the press and the food experts, it is customer satisfaction rating for this service that is trustworthy. This is the reason why the researcher carry out the study: Customer satisfaction rating for the catering service at the Pizza 4P’s Hanoi restaurant